Educação musical e estágio supervisionado: trilhas formativas na construção da docência-estagiária - Abreu, Washington Nogueira de (2023)
The objective of this thesis is to understand the formative process of construction of intern-teaching by student-internships, their challenges and teaching understandings experienced in the COVID-19 pandemic. We start from the assumption that the student-internship involvement with Education and Music is linked to a set of mobilized, lived and internalized experiences, both in higher education and in other situations, which constitute potentializing trails paths for the construction of teaching in the supervised internship, which is called teaching-internship. As specific objectives, we sought to know how experiences of student-interns in Music at UFRN, in the stage of carrying out the last internship, are constructed and internalized; analyze what knowledge, learning and confrontations were mobilized and articulated by studentinterns in the context of the COVID-19 pandemic and understand how teaching is constructed by interns of the Music course and how this construction enhances a definition of teaching-internship. The research is based on the concepts of supervised internship found in studies by Pimenta and Lima (2018), Gaulke (2017), Zabalza (2014), Bolzan (2013), Vaillant and Marcelo García (2012); in the concept of experience, developed by Larrosa (2002; 2006; 2018); in initial formation, addressed by Roldão (2017) and Cunha (2016), and in the concept of teaching, presented by Marcelo García (2012), as well as in the concept of self-formation by Ferry (2004). The work is based on the (auto)biographical perspective of authors such as: Abrahão (2003); Passeggi (2008; 2011; 2016); Passeggi e Souza (2019) and adopts for the analysis of empirical data the comprehensive-interpretive perspective proposed by Souza (2014) allied to the Ricoeurian perspective (2007) on formative memories. Six students of the Degree in Music from a federal university participated in the research. The results of the analyzes highlight the power of the narratives of the student-interns of the Degree in Music at UFRN for understanding the teaching-intern from their formative trails paths. The experiences in formative trails, before and during graduation, were potential in the formative process of construction of the internteaching. Thus, the intern-teaching is defined from moments lived, experienced, internalized and reflected by the student-intern in the supervised internship that, in some way, modify the ways of thinking and acting, in processes of self-formation. In view of this, based on their interest, zeal and willingness, student-interns allow themselves to be attentive to the construction of experiences that give sense and meaning to their training as ideas, behaviors, reflected actions. In a way, the personal and academic lived experiences potentiated encounters, mobilizations and internalizations that are thought triggers at all times of initial formation, especially in the supervised internship.